PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max L.) AKIBAT FREKUENSI PENYIRAMAN DAN BERBAGAI KOMPOSISI PUPUK KANDANG SAPI DAN KOMPOS ECENG GONDOK - Hana Septiaswin; Eny Fuskhah; Susilo Budiyanto (BUANA SAINS, 2021)
The purpose of this research was to study the growth and production response of soybean, which was application use various watering frequencies and the application of water hyacinth compost. The design of this research using Randomized Complete Block Design factorial 3x6 with three replication. The first factor is the frequency of watering (P), that is P1 (once a day), P2 (once in two days), and P3 (once in three days). The second factor is the composition of water hyacinth compost (K), that is K1 (NPK Mutiara), K2 (100 % manure), K3 (25% manure + 75% water hyacinth compost), K4 (50% manure + 50% water hyacinth compost), K5 (75% manure + 25% water hyacinth compost), and K6 (100% water hyacinth compost). The result showed the frequency of watering and the composition of water hyacinth compost could increase the number and weight of pods, also the number and weight of seeds. The treatment with once-a-day watering frequency and 25% manure + 75% water hyacinth compost cause the best and efficient increase in the growth and production of soybean varieties Anjasmoro.